Distribution of bioactive compounds in maize fractions obtained in two different types of large scale milling processes. (September 2017) - Blandino, Massimo; Alfieri, Michela; Giordano, Debora; Vanara, Francesca; Redaelli, Rita
Abstract: Maize kernels contain different bioactive compounds that are important for human health. The aim of this study was to analyze the distribution of the bioactive compounds in maize fractions derived from two industrial dry-milling processes, characterized by a dry-degermination (DD) system and a tempering-degermination (TD) system. The bioactive compounds in maize resulted unevenly distributed in the milling fractions of the kernel. By-products such as the germ and the animal feed flour, had higher total antioxidant capacity (TAC), total polyphenol content (TPC) and total dietary fibre content (TDF) than the whole grains, while xanthophyll and resistant starch resulted to be higher in the fractions derived from the vitreous endosperm. The germ fraction showed also the highest folate content. Results also showed that the type of degermination process influences the bioactive compound contents in the milling fraction, in accordance to the effectiveness of the germ and bran removal from the endosperm fractions. In particular, the animal feed flour obtained by means of TD system resulted in a higher TAC, TPC and TDF than the same fraction obtained by means of the DD system. Conversely, the extraction rate do not affect the recovery of bioactive components in particular fractions. Highlights: Bioactive compounds are unevenly distributed in the maize milling fractions. Germ and animal feed flour had the highest antioxidant capacity and polyphenol content. Xanthophyll and resistant starch are concentrated in the endosperm-derived fractions. Tempering degermination is more efficient in the separation of fine fractions. Extraction yield did not affect the bioactive content distribution.